OP0047 Circulating cd24hicd38hi regulatory b cells influence th17 cell responses in patients with anca-associated vasculitides. (12th June 2018) - von Borstel, A.; Lintermans, L.L.; Heeringa, P.; Rutgers, A.; Stegeman, C.A.; Sanders, J.S.; Abdulahad, W.H.
Abstract : Background: CD24 hi CD38 hi regulatory B cells (Bregs) exhibit suppressive function and modulate pathogenic T cell responses. Persistent expansion of pathogenic IL-17-producing T cells (Th17) has been demonstrated in patients with anti-neutrophil cytoplasmic autoantibody (ANCA)-associated vasculitides (AAV). In addition, a reduction in numbers of CD24 hi CD38 hi Bregs was described in active AAV patients whereas no difference was found in patients in remission compared to healthy controls (HCs). Objectives: To investigate whether there is a direct relation between increased proportions of Th17 cells and diminished proportions Bregs in AAV patients. Methods: Frequencies of both Bregs and Th17 cells were determined by FACS in blood samples from 44 AAV patients in remission. None of the AAV patients received immunosuppressive treatment. Bregs were defined within the CD19 + population as CD24 hi CD38 hi cells, and Th17 cells were defined within the CD3 + CD4 + CD45RO + population by their specific chemokine receptor expression as CXCR3 - CCR4 + CCR6 + cells. In addition, CD3 + CD4 + Th cells were sorted from 4 AAV patients and 3 HCs and co-cultured with either Breg-depleted B cells or total B cells. Cultured cells were stimulated with SEB and CpG-ODN and frequencies of both IL-17 + (Th17) and IFNγ + (Th1) T cells were determined at baseline and day 5 upon restimulation with PMA and Ca 2+ ionophore. Results: The frequency of circulating Bregs in AAV-patients correlated negatively with circulating Th17 cells (r=-0.390; p=0.009), whereas no such correlation was observed with other B cell subtypes. The co-culture experiments revealed that the frequency of IFNγ + Th cells was unaffected when Bregs were depleted in both HCs and AAV patients (undepleted samples median: 10.6%; range: 5.5%–19.7% vs Breg-depleted samples median: 11%; range: 4.9%–19.2%). Remarkably, a significant increase in the frequency of IL-17 + Th cells was detected in Breg-depleted samples (median: 1.6%; range: 1%–3.8%) compared to undepleted samples in both HCs and patients (p=0.03; undepleted samples median: 1.2%; range: 0.9%–2.9%). Moreover, the IFNγ + :IL-17 + T cell ratio was not different between undepleted (median: 13.8, range: 5.1–39.3) and Breg-depleted samples at baseline (median: 11, range: 7.3–30), whereas a significant decrease was found in the Breg-depleted samples (median: 5.6; range: 3.3–9.1) after 5 days of culture (p=0.016; undepleted median: 6.3; range: 4.2–10.6) indicating a change in the Th1:Th17 ratio. Conclusions: CD24 hi CD38 hi Bregs modulate Th17 responses in AAV patients. Future treatment of AAV could aim at expanding CD24 hi CD38 hi Bregs to suppress pathogenic Th17 cells. Disclosure of Interest: None declared